Trade off Theory Testing on Company Capital Structure Compass Stock Index 100 - Denni Hutapea; Munawarah Munawarah; Angelia Cunata; Calvin Calvin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The research objective was to determine the effect of asset structure, profitability, company size and sales growth on capital structureKompas Stock Index Company 100. Quantitative research approach with explanatory types of research. There are 100 companies in Kompas 100 with the use of a sample of 40 companies with a total of 200 observational data. The result is that the asset structure, profitability, firm size have an effect oncapital structure Kompas Stock Index Company 100. Sales growth has no effect oncapital structure Kompas Stock Index Company 100. Asset structure, profitability, company size and sales growth have an effect on capital structure Kompas Stock Index Company 100.